PENGARUH DEBT EQUITY RATIO, PERTUMBUHAN ASET, PERPUTARAN MODAL KERJA, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS - Desy Mariani (Jurnal Akuntansi dan Keuangan, 2019)
Profitability shows the company’s ability to make a profit, one of the measuring instruments used in determining the level of profitability is Return On Asset (ROA). This study aims to analyze the effect of Debt Equity Ratio, asset growth, working capital turnover, and corporate social responsibility on profitability. The population in this study used secondary data as many as 156 companies. Sampling using purposive sampling method found 101 companies, Manufacturing Companies Listed On The Indonesian Stock Exchange For The Period 2015-2017. The analysis technique uses multiple linear regression analysis. The results of the test variable Debt Equity Ratio and variable asset growth have an effect on profitability, while the working capital turnover and corporate social responsibility variables have no effect on profitability.